The General Position of Harput and Its Frame in Chalcolithic Age - Arslantaş, Yüksel (Fırat University, 2014)
Reginol cultures had developed in Eastern Anatolia. But the setlements of Harput and its frame had established relationship with another region. The Cultures of Tell Halaf and Ubeyd had diffused in Harput region in Chalcolithic Age. There were a lot of mineral springs in Harput region and the commercial relationship had been developed with Mesopotamia, Suria and Central Anatolia

Kalkolitik Çağ’da Doğu Anadolu’da bölgesel kültürler gelişmiştir. Harput ve çevresi bu bölgesel kültürlerle ilişki kurmakla birlikte uluslararası ilişkiler de geliştiren bir bölge olmuştur.Bölge Kalkolitik Çağ’ın önemli kültürlerinden Tell Halaf ve Ubeyd kültürlerinin etki sahası içinde kalmıştır. Özellikle bölgede maden kaynaklarının varlığı Mezopotamya, Suriye ve Orta Anadolu ile maden ticaretine dayalı münasebetleri olmuştur
KALKOLİTİK ÇAĞ’DA HARPUT VE ÇEVRESİNİN GENEL VAZİYETİ